Web-based Biodiversity Citizen Science Database (assembled 2012) - Elinore J Theobald; Ailene K Ettinger; Hillary K Burgess; Lauren B DeBey; Natalie Schmidt; Halley E Froehlich; Cherie Wagner; Janneke HilleRisLambers; Josh Tewksbury; Melanie A Harsch; Julia K Parrish (PANGAEA, 2014)
The collective impact of humans on biodiversity rivals mass extinction events defining Earth extquotesingles history, but does our large population also present opportunities to document and contend with this crisis? We provide the first quantitative review of biodiversity-related citizen science to determine whether data collected by these projects can be, and are currently being, effectively used in biodiversity research. We find strong evidence of the potential of citizen science: within projects we sampled (n = 388), ~1.3 million volunteers participate, contributing up to US Dollar 2.5 billion in-kind annually. These projects exceed most federally-funded studies in spatial and temporal extent, and collectively they sample a breadth of taxonomic diversity. However, only 12% of the 388 projects surveyed obviously provide data to peer-reviewed scientific articles, despite the fact that a third of these projects have verifiable, standardized data that are accessible online. Factors influencing publication included project spatial scale and longevity and having publically available data, as well as one measure of scientific rigor (taxonomic identification training). Because of the low rate at which citizen science data reach publication, the large and growing citizen science movement is likely only realizing a small portion of its potential impact on the scientific research community. Strengthening connections between professional and non-professional participants in the scientific process will enable this large data resource to be better harnessed to understand and address global change impacts on biodiversity.
Supplement to: Theobald, EJ et al. (2015): Global change and local solutions: Tapping the unrealized potential of citizen science for biodiversity research. Biological Conservation, 181, 236-244, https://doi.org/10.1016/j.biocon.2014.10.021